Effects of pH on Double Stranded RNA Stability in European Corn Borer Nucleases - Biondi, Marie; Cooper, Anastasia; Song, Huifang; Yu, Zhitao; Zhu, Kun Yan (My University, 2019)
RNA interference (RNAI) is an immune response that can be exploited to make greener pesticides. It works by inciting suppression of a specific target gene using fed or injected dsRNA. Targeting a specific gene sequence also means RNAi can be used to target a specific organism. However, some insects, such as lepidopterans, have nucleases, called dsRNases, in their gut and hemolymph that sever dsRNA and lower RNAi efficiency (1). Ostrinia nubilalis, the European corn borer, (ECB), is a prime example of a lepidopteran pest which decimates corn supplies across the Midwest and does not respond to RNAi. Comparison of dsRNA stability in dsRNase genes in ECB and western corn rootworm (WCR), a coleopteran pest that has very high RNAi efficiency, indicates that dsRNA is rapidly degraded in ECB tissues, but not WCR tissues, despite similar expression of dsRNase genes in both species. These findings suggest that another variable, such as pH may be influencing dsRNA stability in insects (2).
Keywords: USDA NIFA 2019-67032-29071